2015
DOI: 10.1071/an13286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inulin and mannan-oligosaccharides compared with zinc-bacitracin on growing performance, nutrient digestibility and hematological profiles of growing rabbits

Abstract: The study aimed to evaluate the effect of inulin and mannan-oligosaccharides (MOS) vs zinc-bacitracin (ZnB) on rabbit growth performance, nutrient digestibility, and blood profiles. In total, 108 rabbits 32 days of age were divided into four homogeneous groups fed the same basal diet and submitted to the following dietary treatments: control group, without supplementation; inulin group, supplemented with inulin (0.25 g/rabbit.day); MOS group, supplemented with MOS (0.083 g/rabbit.day); and ZnB group, supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…In order to further upgrade the food waste diets, prebiotic fibers were incorporated into the diets to investigate their effects on fish growth as well as non-specific immune response. Prebiotic fiber has been suggested as an alternative to replace antibiotics, for improving the health of animals (Attia et al 2014(Attia et al , 2015aRingø et al 2010). This is because there are many problems associated with the use of antimicrobial agents in aquaculture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further upgrade the food waste diets, prebiotic fibers were incorporated into the diets to investigate their effects on fish growth as well as non-specific immune response. Prebiotic fiber has been suggested as an alternative to replace antibiotics, for improving the health of animals (Attia et al 2014(Attia et al , 2015aRingø et al 2010). This is because there are many problems associated with the use of antimicrobial agents in aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…Inulin is commonly found in different plant species. Various studies had shown that inulin supplement could have positive effects on animal growth and/or innate immune response (Attia et al 2015a;Ibrahem et al 2010). Ibrahem et al (2010) reported that Nile tilapia treated with 5 g inulin per kg diet had significantly higher body weight gain, specific growth rate, condition factor, survival rate, and nitroblue tetrazolium (NBT) value.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of the feed offered (FO) was R$ 0.70/kg, and the gross margin (GM) was calculated by subtracting the costs of bedding and FO from the SP. The methodology was based on a study by Attia et al (2014), as follow: …”
Section: Methodsmentioning
confidence: 99%
“…The first group was placed in an independent temperature-controlled room at 23 ± 2 • C. The broiler chicks from the second group were placed in a heat-stressed room and exposed to chronic heat stress conditions (32 ± 2 • C) for seven hours per day from 8:00 a.m. to 3:00 p.m. The indoor relative humidity and temperature under thermoneutral conditions during the experimental period for the broiler was 51.2% and 23.1 • C, 57% and 23.9 • C, and 53% and 24.7 • C during days [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and 34-41 of age, respectively. Under chronic heat stress conditions, the indoor relative humidity and temperature was 44.9% and 31.5 • C, 47.8% and 31.8 • C, and 41.8% and 31.9 • C during days [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and 34-41 of age, respectively.…”
mentioning
confidence: 99%